Population Administration Services: Realizing Quality Service - Uyun , Inarotun (Universitas Negeri Semarang, 2024)
The objective of this research is to analyze the quality of public services in the field of population administration, particularly the family card services at the Rejosari Barat Village Office. This study employs qualitative descriptive research. The informants of this study total 12, consisting of 2 officials and 10 service users. Data collection techniques include observation, interviews, and documentation. The data analysis used involves data reduction, data presentation, and drawing conclusions. The results show that some criteria are not yet optimal, namely the requirements and service completion times which are unclear and uncertain. The Security indicator is already optimal. The Openness indicator is not yet optimal, as officials are not transparent about service information. The Efficiency, Economy, and Equal Justice indicators are already optimal. The Timeliness indicator is not yet optimal, as the time frame provided does not comply with the Standard Operating Procedure (SOP). The Quantitative Criteria indicator has two criteria that are not yet optimal: the use of modern technology and the increasing frequency of complaints each year. The conclusion of this study is that the implementation of population administration services, particularly family card services at the Rejosari Barat Village Office, is not yet fully optimal. The recommendations given include installing SOP banners, improving facilities and infrastructure, enhancing employee openness, and increasing employee training.